Histological characterization of pulp regeneration using decellularized human dental pulp and mesenchymal stem cells in a feline model - Tan, Yen Yee; Abdullah, Dalia; Abu Kasim, Noor Hayaty; Yazid, Farinawati; Mahamad Apandi, Nurul Inaas; Ramanathan, Anand; Soo, Eason; Radzi, Rozanaliza; Teh, Lay Ann (Elsevier, 2024)
Regenerative endodontics aims to restore pulp tissues, thus preserving the vitality of the tooth. One promising approach involves the utilization of decellularized human dental pulp (DHDP) as a scaffold repopulated with Wharton's Jelly mesenchymal stem cells (WJMSCs). This study aimed to regenerate pulp tissues using DHDP and WJMSCs following pulpectomy in mature canine teeth of a feline animal model and to investigate the histological features of the regenerated pulp. A 12-month-old male domestic shorthaired felines were used as subjects. Teeth were categorized into untreated (Group 1), pulpectomy with mineral trioxide aggregate (MTA) (Group 2), and pulpectomy with DHDP-repopulated scaffold and MTA (Group 3). The animals were sacrificed six weeks post-intervention. H&E and immunohistochemistry using anti-collagen type 1 and laminin antibodies were used to stain the tissue sections. Histological examinations presented pulp-like tissues in Group 3, with tissue components similar to the structures found in Group 1. Immunohistochemical analysis demonstrated the presence of collagen type I and laminin within the regenerated tissues. The root canals of teeth in Group 2 were devoid of pulpal tissue. DHDP with WJMSCs can potentially be used for pulp regeneration, supporting the modality for developing new clinical protocols in stem cell therapy.